THE PRINCIPLES OF FORMATION OF THE PARAMETRIC COMPONENTS OF THE TERMINATION CONTROL SYSTEM OF THE UNMANNED AERIAL VEHICLE FLIGHT PATH - Kondrashov, Ya. V.; Arutyunyan, A. K.; Kravchyshyn, I. O. (Science-based technologies, 2009)
The principles of formation of the vector of distance D from unmanned aerial vehicle UAV to transponderbeacon,and its velocity Vk, which are necessary for on board calculation of the UAV motion parameters.